N.I. Vorobyev and his role in the formation of academic Tatar studies in Russian ethnology - Svetlana V. Suslova (Историческая этнология)
The most important role in the formation of academic Tatar studies in domestic ethnology belongs to the outstanding scholar of the early-mid 20th century, Professor N.I. Vorobyev. With his works, he laid the foundations for a systematic approach to the study of the culture and life of the people, especially the reference group of the ethnic group – the Kazan Tatars. The use of data from related historical and geographical disciplines allowed him to pose and solve a number of important questions in the ethnic and ethnocultural history of the people. In his landmark monograph The Kazan Tatars (1953), special attention is given to their close root connection with the local Bulgarian civilisation – the ethnocultural prehistory of the people. The systematic approach consisted of the creation of N.I. Vorobyev’s first ethnocultural differentiation of the Volga-Ural Tatars, which was based on the cultural, everyday and linguistic differences within the ethnic group studied at that time. It was also manifested in the application of typological approaches to the classification of ethnographic material, which allowed him to present stable varieties of material culture (types) in dynamics, to outline analogues for them in other neighbouring and distant ethnic groups of Eurasia, and thereby to resolve a number of issues related to the cultural genesis of the people. The systematic approach was applied and improved in the research and scientific and organizational activities of his students and followers, including the authors of the volume “Historical and ethnographic atlas of the Tatar people”. Fundamental works of N.I. Vorobyev on the ethnography of the Volga-Ural Tatars laid the foundation for the formation of the Turkic-Tatar vector of academic ethnology in the Volga-Ural region of Russia. They are an invaluable resource for current and future generations of researchers.